Cytotoxic chemical compounds from Labisia pumila - Muhamad, Musthahimah (2017)
Labisia pumila (Myrsinaceae), locally known as Kacip Fatimah is an important medicinal herb in Malaysia. The aim of this study is to identify cytotoxic compounds from the leaves of L. pumila. The leaves were extracted with aqueous methanol and partitioned sequentially with n-hexane and chloroform. The hexane extract has led to isolation of five known alkylresorcinol derivatives, 5-(pentadec-10’-(Z)-enyl)- resorcinol or irisresorcinol (161), belamcandol B (163), 1-O-methyl-6-acetyl-5- (pentadec-10’-(Z)-enyl) resorcinol (164) and 5-pentadecyl resorcinol (10) and 5- (heptadec-12’-(Z)-enyl) resorcinol (201), along with one dimeric 1,4-benzoquinone derivative, demethylbelamcandaquinone B (166). This is the first report on the isolation of 5-(heptadec-12’-(Z)-enyl) resorcinol (201) with a C₁₇ alkenyl side chain from the leaves of L. pumila. Five of the compounds, namely5-(pentadec-10’-(Z)- enyl)-resorcinol or irisresorcinol (161), belamcandol B (163), 1-O-methyl-6-acetyl-5- (pentadec-10’-(Z)-enyl) resorcinol (164) and 5-pentadecyl resorcinol (10) and 5- (heptadec-12’-(Z)-enyl) resorcinol (201) exhibited significant cytotoxic activity against HL-60 human promyelocytic leukemia cells with IC₅₀ value less than or equal to 20 µM. 1-O-methyl-6-acetyl-5-(pentadec-10’-(Z)-enyl) resorcinol (164) exhibited the strongest cytotoxic activity against HL-60 cells with an IC₅₀ value of 1.4 µM. The positive control, etoposide exhibited an IC50 value of 15.3 µM against HL-60 human promyelocytic leukemia cells. In conclusion, the compounds from L. pumila exhibited significant cytotoxic activity.